FROM TOOTH TO TETANUS: A CASE REPORT ON TETANUS FOLLOWING AN ODONTOGENIC INFECTION - Cindy Aprilia Eka Prasanty; Gianina Angelia Santoso; Nikmatul Choiriyah (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Tetanus is an infectious nervous system disease characterized by increased muscle tone, caused by the toxin of the bacterium Clostridium tetani (C. tetani). Tetanus infection generally starts from contaminated open wounds. However,we have found an unexpected consequence of tetanus with odontogenic infection as a potential port of entry. A sixty-year-old male patient with a cavity in the second molar of the lower right region complained of weakness and fever since one day before admission to the hospital. The patient's tetanus immunization status was unknown. On the first day of treatment, the patient's complaints progressed to jaw stiffness, inability to open the mouth, difficulty swallowing solid and liquid food, and stiff neck. Clinical signs showed trismus of 1 cm, stiff neck without meningeal signs, and abdominal muscular defense. The patient was diagnosed with tetanus based on clinical findings. Patient stabilization was initiated early to address the shock condition. The patient was administered human tetanus immunoglobulin 3000 IU intramuscularly in the gluteus, intravenous antibiotics ceftriaxone 1 g every 12 hours, and metronidazole 500 mg every 8 hours, diazepam through a syringe pump at a rate of 40 mg/24 hours, nasogastric tube placement, symptomatic and supportive therapy. The patient was admitted to a dark and quiet tetanus isolation room. Rapid diagnosis confirmation and appropriate therapy administration played a crucial role in determining prognosis. As a result, the patient survived and showed clinical improvement after five days of treatment.